Dividing the Pie: Parties, Institutional Limits, and State Budget Trade-Offs. (June 2019) - Yu, Jinhai; Jennings, Edward T.; Butler, J. S.
Abstract : Although many studies on budgetary outcomes of state politics focus on budget sizes, budget trade-off studies focus on budget composition. This study examines the role of state politics in explaining budget trade-offs. We apply Peterson's typology to analyze budget trade-offs among developmental, allocational, redistributive, and educational expenditures. We focus on the roles of partisan and ideological factors and their interactive effects with institutional limits. Results show that politics matters. The Democratic Party and liberal citizen ideology increase state spending in redistribution relative to other categories, while the Republican Party shifts state budgets toward developmental spending. Partisan effects increase when tax and expenditure limits become less restrictive. Using more recent data and improved measurements, this study explains trade-offs among theoretically meaningful expenditure categories with a comprehensive model while providing a test of Peterson's typology.